A Base Line Survey on the Status of Quality of Drinking Water Resources and Its Contaminants of theDistrict Shaheed Benazirabad, Sindh, Pakistan - Abdul Jabbar Kandhro1, Abdul Manan Soomro2,Muhammad Saleh Khaskheli3,Masood Ali Qureshi4, Nazia Azam Yousfani5, Noor Ali Samoon6,Atta Muhammad Chandio7 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2019)
Objective: The present study was performed to assess drinking water quality and its impacts on health risk assessment in the District Shaheed Benazirabad, Sindh, Pakistan.The study can also provide information about the possible causes of water pollution to increase the public awareness. Study Design: Experimental and Descriptive Cross-sectional Study. Place and Duration of the Study: All the experiments was carried out at Water Testing & Research Laboratory, Department of Community Medicine, PUMHSW-Nawabshah.The study aimed to analyze the groundwater samples were collected from Taluka Sakrand, District Shaheed Benazirabad from Jan. 2018 to Mar. 2018. Material and Methods: Local residents of the Taluka are using bore wells, electric pumps, hand pumps and tube wells. One hundred and sixty five (165) groundwater samples were collected from Taluka Sakrand. Analysis of different chemical characteristics of water samples was performed with portable conductivity meter Orion Star A 322 in the field. pH was measured by portable Orion Star A 321 pH meter.Alkalinity, total Hardness, Cl, 504. Na, K, Ca, Mg, Cu, Co, Mn, Zn, Fe, Pb, Ni and Cd were estimated by (HACH) DR 3900 Spectrophotometer. Arsenic was estimated using (Merck Arsenic field testing Kit (0.01-0.5 mg/1) Darmstadt, Germany). Results:The results; this work reports the analysis of groundwater samples from District Shaheed Benazirabad located at the center of Sindh Province. The samples analyzed were compared with standard values of WHO for drinking water.The physical & chemical parameters of the groundwater samples had the ranges, pH 6.52-8.31, electrical conductivity 357-3780 pS/cm total dissolved solids (TDS) 228-1996 mg/L, HC 3 94-1190 mg/L, total hardness (TH) 115-1275 mg/L, chloride 35-582 mg/L, S 4 24-697 mg/L respectively. The concentration of essential metal ions (Na, Ca, Mg and K) was found in the ranges 30-682 mg/L, 15-283 mg/L, 13-186 mg/L and 3- 62 mg/L respectively. The concentration of Heavy metals was found in the ranges Cu 30-1690 pg/L, Co 2-45 pg/L, Mn 5-198 pg/L, Zn 20-300 pg/L, Fe 40-925 pg/L, Pb 3-125 pg/L, Ni 5-90 pg/L, Cd 3-35 pg/L and As 5- 100 pg/L. Conclusion: The analysis revealed that in a number of ground water samples (50.30 %) studied majority of the parameters were above the upper limit prescribed by WHO. A large number of sites had groundwater samples which were highly contaminated with toxic metals. The high salt concentration in the drinking water of Taluka Sakrand suggests a further research work and some action plans must be implemented to resolve this problem. The results of the examination would make environmental awareness to people of the study area.